Examining the Effectiveness of Provider Incentives to Increase CRC Screening Uptake in Neighborhood Healthcare: A California Federally Qualified Health Center. Issue 6 (November 2020) - Barajas, Melissa; Tangka, Florence K. L.; Schultz, James; Tantod, Kulin; Kempster, Ying Marilyn; Omelu, Ndukaku; Hoover, Sonja; Thomas, Melonie; Richmond-Reese, Valerie; Subramanian, Sujha
As an awardee of the Centers for Disease Control and Prevention's Colorectal Cancer Control Program, the California Department of Public Health partnered with Neighborhood Healthcare to implement evidence-based interventions and provider incentives (incentives offered to support staff, e.g., medical assistants, phlebotomists, front office staff, lab technicians) to improve colorectal cancer screening uptake. The objective of this study was to evaluate the effectiveness and cost of the provider incentive intervention implemented by Neighborhood Healthcare to increase colorectal cancer screening uptake. We collected and analyzed process and cost data to assess fecal immunochemical test (FIT) kit return rates to the health centers and the number of completed FIT kits. We estimated the costs of the preexisting interventions and the new interventions. Analyses were conducted for two time periods: preimplementation and implementation. Most Neighborhood Healthcare health centers experienced an increase in the percentage of FIT kit returns (average of 3.6 percentage points) and individuals screened (an average increase of 111 FIT kits per month) from the baseline period through the implementation period. The cost of the incentive intervention for each additional screen was $66.79. In conclusion, the results indicate that incentive programs can have an overall positive impact on both the percentage of FIT kits returned and the number of individuals screened.